The Omicron (B.1.1.529) SARS-CoV-2 variant of concern also affects companion animals - Sánchez-Morales, Lidia; Sánchez-Vizcaíno, José M.; Pérez-Sancho, Marta; Domínguez, Lucas; Barroso-Arévalo, Sandra (Frontiers in Veterinary Science, 2022)
The emergence of the Omicron variant (B.1.1.529) has brought with it an increase in the incidence of SARS-CoV-2 disease. However, there is hardly any data on its incidence in companion animals. We have detected the presence of this new variant in domestic animals (dogs and cats) living with infected owners in Spain. None of the RT-qPCR positive animals (10.13%) presented any clinical signs and the viral loads detected were low. In addition, the shedding of viral RNA lasted a short period of time in the positive animals. Infection with this variant of concern (VOC) was confirmed by RT-qPCR and sequencing. These outcomes suggest a lower virulence of this variant in infected cats and dogs. They also demonstrate the transmission from infected humans to domestic animals and highlight the importance of active surveillance as well as genomic research to detect the presence of VOCs or mutations associated with animal hosts.